Strategy to Improve the Competence of Alumni of the Department of Management IPB University Using Tracer Study - Sevanya Sagala; Lindawati Kartika (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
This study aims to formulate strategies for improving the competencies of alumni from the Department of Management, IPB University, using tracer study data from cohorts 53–57 (graduates of 2016–2020). The study has three main objectives: (1) to identify learning activities considered most beneficial and the competencies mastered based on the graduates’ learning outcomes; (2) to assess the relevance of alumni competencies to current labor market needs; and (3) to analyze alumni preferences toward the Department of Management as a platform for competency development. The research employed a quantitative approach with purposive and snowball sampling techniques, involving 154 alumni as respondents. Data were analyzed using descriptive statistics, Importance Performance Analysis (IPA), and Net Promoter Score (NPS). The results indicate that the Kuliah Kerja Nyata (KKN) is a learning activity that provides considerable benefits. Communication skills emerged as the top priority for improvement, as reflected in their position within the “concentrate here” quadrant of the IPA analysis. The NPS results show that alumni demonstrate good loyalty. Recommendations include strengthening skills through internship programs in companies where alumni work or within relevant university units